A Case Study of the Factors Affecting Public University Faculty’s Participation in OpenCourseWare - Chang-Hwa Wang; Cheng-Ping Chen; Shi-Ze Hu (Jiàoyù zīliào yǔ túshūguǎn xué, 2013)
This study aims to better understand the key factors affecting the decisions of university faculties to participate in the OpenCourseWare (OCW) and to discuss the promotional strategies. The target university is located in Taipei City and is one of the major OCW providers in Taiwan. Nine instructors participated in the OpenCourseWare were interviewed. The research findings exhibited that the key factors affecting instructor’s willingness to participate in the OCW included altruistic behavior, motivator, honor, time pressure, etc. The study also suggested a series of promotional strategies that may encourage more instructors to participate in OCW.